2019
DOI: 10.3906/vet-1908-16
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic survey of Neosporacaninum infection in aborted fetuses in the Middle Black Sea Region and Sivas Province, Turkey

Abstract: Neospora caninum is a major, cosmopolitan, protozoan parasite associated with abortion in cattle and water buffaloes. In this study, real-time PCR was used for the detection and quantification of the burden of N. caninum infections in aborted fetuses in the Middle Black Sea Region and Sivas Province of Turkey. In total, N. caninum DNA was detected in 44 of the 89 (49.4%) aborted fetuses of the cattle and water buffalo from 89 different farms. The authors conclude that the pervasiveness of neosporosis is a thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, DNA detection in aborted fetuses is not sufficient to confirm that N . caninum is responsible for reproductive failure because other abortifacient factors may also play a potential role in abortion [ 106 ]. Although PCR is one of the most accurate and widely used molecular methods to study the global prevalence of N .…”
Section: Discussionmentioning
confidence: 99%
“…However, DNA detection in aborted fetuses is not sufficient to confirm that N . caninum is responsible for reproductive failure because other abortifacient factors may also play a potential role in abortion [ 106 ]. Although PCR is one of the most accurate and widely used molecular methods to study the global prevalence of N .…”
Section: Discussionmentioning
confidence: 99%
“…DNA from N. caninum was detected by qPCR in the fetus of one water buffalo from a fetus from a dam that was 2-3 years old, during which abortion occurred between 180 and 210 days of gestation (103); however, the authors concluded that they could not have confirmed if neosporosis was the only cause of abortion because other abortive agents could be present. Consequently, they suggest that N. caninum could be responsible for reproductive failure in water buffalo.…”
Section: Epidemiologymentioning
confidence: 99%